Estrutura e funcionamento dos Conselhos Municipais do Idoso : subsídios para gestão de um Conselho do Idoso - Santos, Flávia Teresa Moreira dos (Universidade Federal de São Carlos, 2017)
To study the Elderly Councils assume in the comprehension of the historical context in which the Councils of Rights appeared. The Elderly Councils are part of a protection network, once they are participative instances in the defense of their rights. In this sense, two important legal lines are highlighted, the National Policies for the Elderly, which institutionalized them, and the Statute of the Elderly, which ratify them. In this way, it is presented the subject of the social participation which refers to sharing the power of decision regarding public subjects in these participative spaces (TATAGIBA 2002, GOHN 2002,2011a), after and before the 1988 Federal Constitution. The objectives of this research are to comprehend the structures and the operation of these Councils, to present the areas in which the demands of the elderly population were evidenced on three Conferences of the Elderly People Rights, and to analyze an Elderly Council located in a city in the State of São Paulo. The research is part of the qualitative methodological framework characterized as a case study (Godoy, 2006). The results demonstrated that it was possible to understand the singularity and particularity that were present in this Council, and from this understanding, a booklet was developed in order to extend the knowledge to other Councils that identify themselves with this problematic. The social relevance of this research is the possibility of presenting an educational action for the members of the Elderly Municipal Council and contribute with the performance of the tasks of the Council members.
Structure and functioning of the Elderly Municipal Councils : subsidies for management of an Elderly Council
Keywords: Conselhos; Pessoas idosas; Participação; Conferências; Ação educativa; Councils; Elderly; Participation; Conferences; Educational action; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS